Chromatographic and Spectrophotometric Determination of Clindamycin in Pharmaceutical Products - Al-Momani, Idrees Faleh; Al-Kilani, Lana Mohammad Zaid (Indonesian Journal of Chemistry, 2024)
Accurate, precise, and reliable chromatographic and spectrophotometric methods were developed for determining clindamycin (CLD) in pharmaceutical formulations. The spectrophotometric method was adopted for flow injection analysis (FIA). The method is based on the online oxidation of CLD and measuring the absorbance of the resulting product using a flow cell at 605 nm. Experimental conditions, including FIA variables and reaction conditions, were optimized. The chromatographic separation was achieved using a C8 column and an isocratic mobile phase. The composition of the mobile phase selected for the analysis consists of a mixture of phosphate buffer (50%), MeOH (35%), and ACN (15%), adjusted to a pH of 3.47 by phosphoric acid. The eluent was monitored with a UV detector at 205 nm. The linearity range was 10–200 and 50–800 µg/mL for the FIA and HPLC, respectively. The applicability of the FIA and HPLC methods was validated by analyzing CLD in synthetic and commercial pharmaceutical products. No significant interferences were observed from the common excipients usually used in commercial formulations.